Pengaruh perbedaan jumlah penambahan binder uretan dan berbagai motif embossing terhadap kualitas kulit reject - Emiliana Kasmudjiastuti; Prayitno Prayitno; Bidhari Pidhatika; Gresy Griyanitasari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2016)
Rejected tanned leather is tanned lether product with damages of more than 30% of its total surface area, but can be improved by embossing. Embossing is the provision of patterns that influences the properties of articles and contributes to the closure of the defects on the surface of leather. This study aims to determine the influence of urethane binder and embossing motives to the quality of rejected leather for shoe upper applications. Variables investigated were urethane binder composition (100, 150, and 200 part in 1000 part of base coat) and embossing motives (crocodile, ostrich, shark fish, and milled motive). The quality of the leather was then tested in terms of organoleptic properties (feel, flexibility, visual appearance), mechanical properties (tear strength, tensile strength, elongation at break, rub fastness (dry, wet), adhesive strength of cover paint (dry, wet), and flexing resistance), physical properties (WVP and WVA), as well as morphology (SEM). The results showed that the addition of urethane binder and embossing patterns affect the quality of shoe upper leather, i.e. in general covering the leather defects and increasing the visual appearance (organoleptic properties), and changing the collagen network structure (based on SEM test). Visually preferred skin is skin with the addition of 200 parts of the urethane binder and crocodile patterned leather.